Pengiriman Daya dari Inverter Lima Tingkat ke Grid Satu Fasa Menggunakan Arduino Due (Jurnal Teknik Elektro, 2020)
Inverter has been used for a wide variety of applications in renewable energy system. The use of inverter in a solar power plant system can off-grid and on-grid. H-Bridge inverter is one of the commonly used inverter. One of its disadvantages is the requirement of high frequency in order to get a low defect level on the output current. The use of a five-level inverter with considering the amount of a power semiconductor switch in can be as an alternative. This study aims to use a five-level inverter with five power semiconductor switches to deliver power to the grid.The working principle uses two sinusoidal signals that are shifted by 1800 compared to two carrier signals to produce a sinusoidal pulse width modulation signal. A sinusoidal pulse width modulation signal is used as a controller on each power semiconductor switch. The transmitted power is in the form of aÂ currentÂ that is injected into the single-phase grid. The transmission of a power using five-level inverter to a single-phase grid was validated by a Power Simulator software. The final stage was a hardware implementation in the laboratory. The result shows that the inverter could transmit a power as current with 4.01% THDi, transmitted power as 36.4 Watts, and transmitted current as 0.52 Amps.